Effectiveness of universal self-regulation-based interventions to improve self-regulation, and effects on distant health and social outcomes in children and adolescents: a systematic review and meta-analysis. (November 2017) - Pandey, Anuja; Hale, Daniel; Das, Shikta; Goddings, Anne-Lise; Blakemore, Sarah-Jayne; Viner, Russell
Abstract: Background: Self-regulation is a psychological construct that encompasses a range of competencies including controlling one's emotions, positive interactions with others, and self-directed learning. Self-regulation is gaining importance as an intervention target because of mounting evidence suggesting its positive impact on health, social, and educational outcomes. In a systematic review, we rigorously evaluated interventions designed to improve self-regulation in children and adolescents. Methods: Keyword searches of the databases PsycINFO, PubMed, EMBASE, CINAHL Plus, ERIC, British Education Index, Child Development & Adolescent Studies, and CENTRAL were performed from inception to July 15, 2016 (seeappendix for search strategy). Eligibility criteria included randomised controlled trials (RCTs) and cluster RCTs, universal interventions for self-regulation in children and adolescents, at least one self-regulation outcome measure, and peer-reviewed publications with full text available in the English language. References of the included articles were also reviewed. Data were extracted on self-regulation and distant outcome measures. All but eight studies were high-to-moderate quality when assessed with the Effective Public Health Practice Project quality assessment tool. Findings: From 14 369 records screened, 147 were identified for full text review, and 50 cluster RCTs and RCTs including 23 098 participants were eligible for final review. Consistent improvement in self-regulation was reported in 16 of the 21 curriculum-based, four of the eight mindfulness and yoga-based, six of the nine family-based, four of the six exercise-based, and four of the six social and personal skills interventions. A meta-analysis of self-regulation task performance scores of intervention group versus controls showed a pooled standardised mean effect size of 0·43 (95% CI 0·35–0·51). Positive impact was reported in 11 of 13 studies studying academic achievement, all three studies reporting conduct disorders, two studies each on social skills, mental health (depression), and behavioural problems, one study on school suspensions, and four of five studies on substance misuse. The follow-up period for such outcomes varied from 1 to 5 years. Interpretation: A wide range of interventions were successful in improving self-regulation in children and adolescents. There was improvement in distant academic, health, and behavioural outcomes in most intervention groups compared with controls. Funding: Department of Health Policy Research Programme.